Nanostructured Antireflection Coatings for Optical Detection and Sensing Applications. Issue 1805 (10th July 2015) - Pethuraja, Gopal G.; Welser, Roger E.; Zeller, John W.; Puri, Yash R.; Sood, Ashok K.; Efstathiadis, Harry; Haldar, Pradeep; Dhar, Nibir K.; Wijewarnasuriya, Priyalal
ABSTRACT: Optical components such as lenses, glass windows, and prisms are subject to Fresnel reflection due to the mismatch between the refractive indices of the air and glass. An optical interface layer, i.e., antireflection (AR) layer, is needed to eliminate this unwanted reflection at the air/glass interface. Nanostructured broadband and wide-angle AR structures have been developed using a scalable self-assembly process. Ultra-high performance of the nanostructured AR coatings has been demonstrated on various substrates such as quartz, sapphire, polymer, and other materials typically employed in optical lenses. AR coatings on polycarbonate lead to optical transmittance enhancement from approximately 90% to almost 100% for the entire visible, and part of the near-infrared (NIR), band. The AR coatings have also been demonstrated on curved surfaces. AR coatings on n-BK7 lenses enable ultra-high light transmittance for the entire visible, and most of the NIR, spectrum. Nanostructured oxide layers with step-graded index profiles, deposited onto the optical elements of an optical system, can significantly increase sensitivity, and hence improve the overall performance of the system.